Resources – performance relationship: the mediating role of enterprise risk management (ERM) in Malaysia / Noraznira Abd Razak - Abd Razak, Noraznira (Institute of Graduate Studies, UiTM, 2017)
This study analyses the relationship between firm resources and its performance while examining the mediating roles of enterprise risk management in the firm resources – firm performance relationship within the context of the Resource-based view theory (RBV) and Donabedian theory. A quantitative approach is employed in this study and responses from 223 risk managers among Malaysian listed firms under Malaysian Bourse were analyzed by using Partial Least Squares (PLS-SEM) technique. The results show that intangible resources are directly related to performance, meanwhile through the mediating effect of enterprise risk management (ERM), an indirect relationship was confirmed. However, tangible resources and capabilities show negative results on the relationship with the performance of the firm and further analysis using ERM as mediator yields the same negative results…